Pengembangan Media Digital Interaktif pendukung Kelompok Kinestetik pada Materi perubahan Wujud Benda Pada Siswa Sekolah Dasar - Purwanti, Camelia Istiqomah; Fanani, Achmad (Jurnal Studi Guru dan Pembelajaran, 2024)
The development of the Industrial Revolution 4.0 has had a changing impact on society, including the world of education. Development of Industrial Revolution 4.0 also coincides with the demands of 21st century learning related to 4 skills namely critical thinking, innovative, collaborative and communicative. Two things requires teachers to conduct learning that focus on the fourth students' skills. Therefore, it needs internal innovation learning, namely by developing interactive digital media. In Determining the media used, teachers must understand the characteristics and style student learning. The research design used research and development 4D models. This interactive digital media product supports the kinesthetic group is a material about phase transition of objects in video file. The results of media suitability by media experts and teachers show an average of 4.67. The results of material suitability by material experts and teachers showed an average of 4.41. The results of the appropriateness of language use by linguists and teachers show an average of 4.17. The results of the average score can be concluded that the media product interactive digital supporting the kinesthetic group is included in the criteria Very good. The student response questionnaire is also validated by lecturers and teachers with an average score of 4.8 and it can be concluded that This response questionnaire is very proper to be used. Besides that, the test questions also got the validation stage by lecturers and teachers with an average score of 4.15 and it can be concluded that the test questions is proper.The next, the media has been validated and revised, then some revisions can be used in the teaching and learning process. As for the results of Student responses with a total of 27 students obtained an average of 3.79 means this media is proper to use. In addition, the results of the average test scores of participants student is 90.93 or the result in percentage is 95% as a very good conclusion. Thus, digital media interactive kinesthetic group support is effective and able to provide impact on improving student learning outcomes in the material namely transition object.